Implementasi Hukum Terhadap Kejahatan Begal Yang Dilakukan Anak Di Bawah Umur Di Bekasi : Studi Literatur Review - Raihan Saputra; Jihan Luthfi Nabillah; Kevin Yazid; Arizki Arizki; Sahrul Layali; Mic Finanto Ario Bangun (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research discusses the implementation of the law against perpetrators of robbery committed by minors in Bekasi. Where this research examines previous research to support the problem formulation. A qualitative research approach was applied. Data was obtained from internet sources such as Google Scholar, Mendeley, DOAJ, and EBSCO. The results of this research include: 1); The role of the police in tackling robbery crimes in Bekasi has been carried out on a massive scale by carrying out patrols in several places where robbery crimes occur 2); The application of the law to perpetrators of robbery committed by teenagers can be applied and given to perpetrators of robbery who are still teenagers or underage. Criminal law plays a role in children as perpetrators of robbery, so children can be punished according to the decision of the judge who examined the case. So that the public can find out whether the law can be given to criminals who are still underage